Knowledge management mechanisms for attrition control in private higher learning institutions - Annamalai, Muthukkaruppan; Md Sabri, Sabiroh; Amin, Salmiah (2012)
Private Higher Learning Institutions (PHLI) are concerned about student attrition because the cost related to the delivery of education is sensitive to the student enrolment. While mentoring is a useful approach for attrition control, such systems are often not well established in PHLI due to high turnover of lecturers who play the role of mentors and are also attributed to weak institutional follow-through. Apropos Knowledge Management(KM) mechanisms can help to equip the mentors with the requisite capabilities, as well as, facilitate the reinforcement of the institutional network and commitment to effectively deal with attrition.Consequently, the paper outlines a systematic approach for implementing an organised array of KM mechanisms for attrition control in PHLI. Our proposal is based on case studies involving two PHLI in Malaysia, analysed according to exemplar student integration and attrition models, and espouses intervention strategies through a mentoring program.